2008
DOI: 10.1037/0021-9010.93.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task performance, helping, voice, and organizational loyalty on performance appraisal ratings.

Abstract: Despite the fact that several studies have investigated the relationship between organizational citizenship behavior and performance appraisal ratings, the vast majority of these studies have been cross-sectional, correlational investigations conducted in organizational settings that do not allow researchers to establish the causal nature of this relationship. To address this lack of knowledge regarding causality, the authors conducted 2 studies designed to investigate the effects of task performance, helping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
310
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 320 publications
(334 citation statements)
references
References 61 publications
18
310
0
6
Order By: Relevance
“…In terms of employee performance, Whiting et al (2008) also found that employees who were seen as loyal were rated as better performers. In contrast, less loyal employees are likely to be viewed with suspicion because of uncertainty as to whether they intend to help the organization.…”
Section: Union Representationmentioning
confidence: 91%
See 4 more Smart Citations
“…In terms of employee performance, Whiting et al (2008) also found that employees who were seen as loyal were rated as better performers. In contrast, less loyal employees are likely to be viewed with suspicion because of uncertainty as to whether they intend to help the organization.…”
Section: Union Representationmentioning
confidence: 91%
“…Interestingly the message that can be deduced from employee empowerment is complimentary to what Whiting et al (2008) are saying, namely that through the process of empowerment/employee participation the employees are more committed to the organization and thus could be more loyal, resulting in managers seeing them as better performers and ending up improving the organization. This is an outcome that provides the organization's justification for granting freedom of association.…”
Section: Union Representationmentioning
confidence: 95%
See 3 more Smart Citations